Edukasi Gizi Masyarakat Dan Cek Kesehatan Gratis Di Desa Jayalaksana - Haqiyah, Aridhotul; Faqih, Ahmad (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam 45 Bekasi, 2024)
Random examination of uric acid levels in the people of Jayalaksana Village, Branchbungin District, Bekasi Regency, West Java aims to educate the public about Nutrition Education as an early detection of emerging diseases. The more people who know about uric acid levels, it is hoped that it can change the behavior of people's food intake and nutrition. So that disease prevention can be reduced, especially in people who have high risk factors. The educational method is carried out by counseling on nutrition and health checks on February 25, 2023 with community subjects, both men and women. The medical examination carried out is to measure the level of blood sugar levels. Based on the activities carried out, the results obtained were 25 respondents. A total of 15 were female and 10 were male. Found in residents who are female as much as 60% and male as much as 55% on blood sugar levels. So it can be concluded that through nutrition counseling and examination of uric acid levels the community can find out the blood sugar level which is used as a reference to regulate healthy and nutritious food intake patterns to reduce the risk of disease